KONSEP DAN APLIKASI SUKUK NEGARA DALAM PEMBIAYAAN DEFISIT APBN DI INDONESIA - Lutfiani, Hilda (Sekolah Tinggi Ilmu Syariah Husnul Khotimah, 2018)
Increasing government spending which is not accompanied by the rise of country Income can cause an enhancement State Budget deficit, so far the government still fond of closing the budget deficit with foreign debt, where foreign debt is never apart from the interest as return arising from the existence of the loan. Where as Islam expressly forbidden usury. Therefore raised the alternative in accordance with the principles of shari'ah which can become a source of financing of the state budget deficit. One of the source of the payment is the sale of State Islamic Bonds or sovereign sukuk that are defined as bonds that is issued based on the principles of sharia as evidence of ownership of the assets in a certain period of time. Based on this, the author want to analyzing sovereign sukuk in financing the deficit of the State Budget. This research aims to know more in the concept of the sovereign sukuk issuance in state budget financing and the knowledge position of sovereign sukuk in state budget deficit in Indonesia. In this research the authors use literature study. To discuss more in and achieve the goal, the author is attempting to collect data both primary and secondary. In the processing of collecting data the authors use the method of observation which is the first step to see and get the necessary data with how to observe the intensively books and other data source. Then analyzed using the way of thinking of the induction assisted with the wrong deductions method to draw a conclusion. In order to analyze which conveyed more depth, author continue analysis using descriptive analysis techniques analysis. This research results that sovereign sukuk potential to be developed as an alternative in accordance with the principles of shari'ah which can become a source of financing the deficit with 3 publishing mechanism, namely Private placement, bookbuilding and auction. Position of sovereign sukuk in state budget deficit in 2010- 2014 is not clear because the deficit increase from IDR 46.8 Trillion to IDR 241.5 Trillion, but in 2014- 2015 budget deficit decrease from IDR 241.5 Trillion to IDR 222.5 Trillion, while the financing of the state budget deficit source from the issuance of the sovereign sukuk on 2014-2015 experiencing an increase of IDR 265 Trillion to IDR 298 Trillion, this describes the issuance of sovereign sukuk can become the main instrument in State Budget deficit financing.